(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the political situation in Turkestan on the eve of national-territorial delimitation, the purpose and essence of the delimitation policy of the authoritarian regime, the ethnic conflicts that occurred in the period after the national-territorial delimitation, how the complex and problematic aspects of the borders of the newly established republics were overcome, as well as Adib Khalid, Edward Studies of ethnic problems in Central Asia by researchers such as Stourton, Peter Zeihan, Francine Hirsch, P. Loung, Alexander Morrison are discussed.